PENGARUH COST DAN BENEFIT SWITCHING TERHADAP RESISTENSI PENGGUNA SISTEM INFORMASI AKUNTANSI DENGAN NILAI PENERIMAAN, DUKUNGAN ORGANISASI, EFIKASI DIRI UNTUK BERUBAH DANOPINI KOLEGA SEBAGAI VARIABEL INTERVENING - Sobrotul Imtikhanah (Neraca, 2014)
The background of this research came from PP 71 tahun 2010 about the statement Government Accounting Standards in attachment 1 which state that basis of accounting used is the accrual basis and there is Permendagri no 64 tahun 2013 about accounting system based on accrual basis which must be implemented no longer than 2015. It also affected in the change of the use of accounting information system which also should be changed. It caused resistance to change of the user in term of that change. This research aimed to get empirical evidence about the costs and benefits of switching to user resistance. The data was collected by questionaire with the treasures as the respondents in Pekalongan and Pemalang. Meanwhile, the variable was measured by Likert-Scale. Then, the collected data was analyzed by Structural Equition Modelling of AMOS software